[Haskell-beginners] arrow type signature question
mhamro at gmail.com
Thu Nov 18 13:43:43 EST 2010
I got it. Thanks a lot. By the way, can you provide with example of using
resultFun or secondFun.
I did search on Hyahoo and Hoogle for names and signatures and I didn't see
On Thu, Nov 18, 2010 at 1:29 PM, Daniel Fischer <daniel.is.fischer at web.de>wrote:
> On Thursday 18 November 2010 18:51:32, MH wrote:
> > Oh, so this signature is really a partial application that expects
> > another parameter to be executed.
> Depends on how you look at it.
> Strictly speaking, there is no such thing as partial application. Every
> function takes exactly one argument, so it's either not applied to any
> argument at all yet or it's fully applied. But the result of a function
> application can be another function, so it may take another argument ...
> However, always talking about functions taking an argument of type a and
> returning a function taking an argument of type b and returning a function
> taking an argument of type c ...
> is terribly cumbersome, so we speak of functions taking several arguments.
> But note that the number of arguments a function takes until the final
> result is no longer a function is not always fixed. For example,
> id :: a -> a takes one argument, obviously, doesn't it?
> But if that argument is a function, it takes one more argument, so id can
> take two arguments, or three, or however many you want, it depends on which
> arguments you pass.
> So when you have a value of type a -> b -> c (which is the same as
> a -> (b -> c), since the function arrow is right-associative), and apply it
> to a value of type a, sometimes it is more appropriate to think of that as
> a partial application, sometimes as a complete application resulting in a
> > So
> > resultFun :: (h b -> h b') -> (h (a->b) -> h (a->b'))
> which is
> resultFun :: (h b -> h b') -> h (a -> b) -> h (a -> b')
> > is
> > foo :: h b -> h b'
> > bar :: h (a->b) -> h (a->b')
> No. bar :: h (a -> b)
> resultFun foo :: h (a -> b) -> h (a -> b')
> so it takes an argument of type h (a -> b) and its result has type
> h (a -> b')
> (which may be another function type, if h x = e -> x).
> > firstFunction = resultFun foo
> > result = firstFunction bar
> > Is this correct?
-------------- next part --------------
An HTML attachment was scrubbed...
More information about the Beginners